Servitization in Malaysian Poultry Contract Farming: A Critical Overview - Nazim Baluch; Ahmad Shabudin Ariffin; Zakaria Abas; Shahimi Mohtar (International Journal of Supply Chain Management, 2017)
The old dichotomy between product and service has been replaced by a service-product continuum. In the management literature this is referred to as the Servitization of Products. This shift in business model is important because it means the interests of clients and providers are much more closely aligned. Broiler meat is the primary and most popular source of dietary protein in Malaysia. Malaysian Broiler poultry meat production in 2015 was 1,520,000 tones, primarily through contract farming. Though the broiler industry has attained high level of productivity and growth with efficient and innovative ways at their credit; the general, mainstream, servitization concept is highly skewed in industrys favour, with minimal attention given to the negative health effects on consumers. In fact, the servitization concept has turned into inimical servitization term contrived by the author. This paper explains the concept of servitization, inimical servitization, and Product Service System (PSS); elaborates on the Malaysian broiler industry production practices; and highlights the health and environmental issues pertaining to broiler meat birds welfare and consumers. Finally the paper concludes that the excessive growth speed creates numerous health and environmental problems for the meat birds and consumers alike. There is a dire need to establish guidelines and mechanism to monitor the production process of the broiler industry in order to safeguard the consumers and meat birds welfare and prevent environmental degradation. Broiler industry should earnestly apply PSS criterion on the broiler supply chain.